1993
DOI: 10.1108/09684889310046176
|View full text |Cite
|
Sign up to set email alerts
|

Observing Classroom Teaching in Higher Education

Abstract: Describes the operation of a scheme to appraise teaching quality through classroom observation at Bournemouth University during 1993. Outlines the principles, design and evaluation of the scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Some of the problems associated with PRT as identified by Hutchings (1996) include issues in publicizing teaching practice, establishing standards of good teaching practice, issues in dividing limited time for PRT and teaching responsibilities, as well as selecting the right methods and reviewers to assess teaching performance. This is supported by research that shows the reliability and validity of feedback from nonspecialist reviewers is persistently questioned although proven otherwise by Hanson (1993). Some faculty members may prefer having expert feedback in addition to peer feedback due to concerns that their peers might be too inexperienced to provide valuable feedback (Bell & Mladenovic, 2008).…”
Section: Potential Problems To Teaching Practicementioning
confidence: 95%
See 4 more Smart Citations
“…Some of the problems associated with PRT as identified by Hutchings (1996) include issues in publicizing teaching practice, establishing standards of good teaching practice, issues in dividing limited time for PRT and teaching responsibilities, as well as selecting the right methods and reviewers to assess teaching performance. This is supported by research that shows the reliability and validity of feedback from nonspecialist reviewers is persistently questioned although proven otherwise by Hanson (1993). Some faculty members may prefer having expert feedback in addition to peer feedback due to concerns that their peers might be too inexperienced to provide valuable feedback (Bell & Mladenovic, 2008).…”
Section: Potential Problems To Teaching Practicementioning
confidence: 95%
“…The question is, "Can reviewers without subject expertise provide equally valid feedback as reviewers who are with subject expertise." Hanson (1993) addressed this concern through a pilot study in a PRT program by having a subject specialist evaluate a group of faculty members. The evaluation revealed that feedback from nonspecialist appraisers and subject specialists are equally reliable and valid.…”
Section: Problem Statementsmentioning
confidence: 99%
See 3 more Smart Citations